Perception of Education Study Program Students Regarding the Use of AI as an Assistive Tool in Creating Coursework - Shantika Regina, Frilia; Pamungkas Alamsyah, Trian (IJORER : International Journal of Recent Educational Research, 2026)
Objective: This study aims to explore the perceptions of students in the Education Study Program regarding the use of AI in completing coursework. The presence of Generative AI such as ChatGPT, Gemini, and various other tools has changed the way students access information, process data, and even compile coursework. The placement of AI as a learning aid needs to be strengthened so that it does not become the primary and sole source used by students. Method: The method used in this study is a quantitative descriptive method. The research data was obtained based on the results of a questionnaire with 16 questions distributed to undergraduate students in the Education Study Program for the 2024/2025 Academic Year. The analysis steps include data tabulation, frequency distribution, and data interpretation. Results: The results show that AI is recognized as massively improving the quality of assignments (83.33%) and the ability to argue logically (77.78%). However, on the other hand, the majority of students (53.71%) realize that this technology triggers laziness in critical thinking. The use of AI also has a positive impact, namely as a personal assistant (87%) which is very effective in streamlining study time (94.45%) and improving material understanding. There is concern among students about plagiarism (92.60%) and recognition that the use of AI without personal contribution is cheating. Novelty: Based on these findings, the integration of AI ethics courses into the university curriculum is necessary. In addition, official guidelines and integrated AI literacy are needed to maintain the academic integrity of prospective educators in the era of digital disruption.